Factors influencing the Diabetes Prevention Behaviors Among Muslim Prediabetes in Yaha District, Yala Province - Makeng, Madiha; Suwan, Kamonwan; Loeknok, Chilawat (Journal of The Royal Thai Army Nurses, 2025)
This predictive descriptive study aimed to identify factors influencing diabetes preventive behaviors among prediabetic Muslims in Yaha District, Yala Province. A total of 383 participants were selected using proportionate stratified random sampling based on the population of individuals at risk of diabetes in each health service unit. The research instruments included a general and health status questionnaire, a health belief questionnaire, and a diabetes preventive behavior questionnaire. The content validity indices of these instruments were .91, .98, and .99, respectively, with a Cronbach’s alpha coefficient of .84. Data were analyzed using descriptive statistics, Pearson’s correlation coefficient, and stepwise multiple regression analysis. The results revealed that overall health beliefs were positively correlated with diabetes preventive behaviors at a low level (r = .298, p < .001). Perceived susceptibility and perceived benefits were moderately positively correlated with preventive behaviors (r = .326, p < .001), while perceived barriers were negatively correlated at a low level (r = –.221, p < .001). The analysis revealed that perceived susceptibility, perceived benefits, and perceived barriers together significantly predicted 15.6% of the variance in diabetes preventive behaviors (R = .403, Seest = 10.985, p < .01). Therefore, promoting awareness of risk and benefits, along with reducing perceived barriers, can help enhance diabetes preventive behaviors and serve as a guideline for developing culturally appropriate health promotion strategies suitable for the target communities.